2013
DOI: 10.1177/0956797613501169
|View full text |Cite
|
Sign up to set email alerts
|

Below-Baseline Suppression of Competitors During Interference Resolution by Younger but Not Older Adults

Abstract: Resolving interference from competing memories is a critical factor in efficient memory retrieval, and several accounts of cognitive aging suggest that difficulty resolving interference may underlie memory deficits such as those seen in the elderly. Although many researchers have suggested that the ability to suppress competitors is a key factor in resolving interference, the evidence supporting this claim has been the subject of debate. Here, we present a new paradigm and results demonstrating that for younge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 36 publications
5
40
0
1
Order By: Relevance
“…Participants tend to show greater forgetting of unpracticed-related items than unpracticed-unrelated items, which has been attributed to the suppression of unpracticed (yet competing) items during the retrieval-practice phase (Anderson et al, 1994). Although other interpretations of the RIF effect have been suggested (e.g., MacLeod, Dodd, Sheard, Wilson, & Bibi, 2003; Raaijmakers & Jakab, 2013), there is mounting evidence from converging methods which suggests that competition at retrieval is resolved by way of inhibition (e.g., Benoit & Anderson, 2012; Healey et al, 2010; Healey, Ngo, & Hasher, 2014; Hulbert, Henson, & Anderson, 2016; Rupprecht & Bäuml, 2016; Storm & Angello, 2010). Given that imagination involves the retrieval of information stored in memory, not all of it relevant to current goals, it is plausible that imagination would produce an inhibitory effect similar to that seen during memory retrieval.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants tend to show greater forgetting of unpracticed-related items than unpracticed-unrelated items, which has been attributed to the suppression of unpracticed (yet competing) items during the retrieval-practice phase (Anderson et al, 1994). Although other interpretations of the RIF effect have been suggested (e.g., MacLeod, Dodd, Sheard, Wilson, & Bibi, 2003; Raaijmakers & Jakab, 2013), there is mounting evidence from converging methods which suggests that competition at retrieval is resolved by way of inhibition (e.g., Benoit & Anderson, 2012; Healey et al, 2010; Healey, Ngo, & Hasher, 2014; Hulbert, Henson, & Anderson, 2016; Rupprecht & Bäuml, 2016; Storm & Angello, 2010). Given that imagination involves the retrieval of information stored in memory, not all of it relevant to current goals, it is plausible that imagination would produce an inhibitory effect similar to that seen during memory retrieval.…”
Section: Introductionmentioning
confidence: 99%
“…By inhibition, we mean reduced availability or activation of the representation itself, not reduced accessibility via a particular retrieval cue (Anderson & Spellman, 1995). In order to test the accessibility of competing concepts, we used a modified priming approach (similar to that of Healey et al, 2014), testing response times (RTs) to associated concepts immediately after future imagining. If related concepts compete and are inhibited during future imagining, then participants should be slower to respond to these concepts on a subsequent task.…”
Section: Introductionmentioning
confidence: 99%
“…Early formulations of the theory suggested that inhibition was an attentional mechanism that regulated the flow of information into and out of working memory. More recent formulations do not assume a dual–store model of memory (Healey, Campbell, Hasher, & Ossher, 2010; Healey et al, 2013; Healey, Ngo, & Hasher, 2014). …”
Section: Aging and Memory Change: The Data And The Theoriesmentioning
confidence: 99%
“…When a item is presented for encoding it triggers a cascade of associated thoughts and memories, many of which are not relevant to the task at hand. Younger adults may use the access function of inhibition to prune this cascade (Healey et al, 2013; Healey, Ngo, & Hasher, 2014). For older adults, an inhibitory deficit may allow these irrelevant thoughts and memories to remain active and become bound to relevant information in memory (e.g., Hamm & Hasher, 1992).…”
Section: Simulating Age–related Memory Changementioning
confidence: 99%
“…Healey, Ngo, & Hasher, 2014). DA at retrieval has been shown to consume attentional resources, as evidenced by large costs to the secondary task (e.g.…”
mentioning
confidence: 99%